Interaction of temperature and light on seed germination in Tecoma stans L. Juss. ex Kunth (Bignoniaceae) - Socolowski, Fábio [UNESP]; Vieira, Daniela Cristine Mascia [UNESP]; Takaki, Massanori [UNESP] (Brazilian Archives of Biology and Technology, 2008)
Os efeitos da temperatura e da luz na germinação de Tecoma stans foram determinados no presente trabalho. Foram testadas temperaturas constantes de 10 a 45ºC, com intervalos de 5ºC, sob luz branca e escuro. Verificou-se que a temperatura ótima para a germinação da espécie está entre 25 e 30ºC, tanto na luz como no escuro, já o intervalo de máxima germinabilidade está entre 15 e 35ºC na luz e 20 e 40ºC no escuro. Suas sementes apresentaram uma maior sincronização da germinação próxima à temperatura ótima. A germinação de sementes de Tecoma stans em condições naturais foi testada sob radiação solar direta e na sombra de vegetação. A maior porcentagem de emergência ocorreu no ambiente de sol (86,1%), porém com menor velocidade em relação à sombra, embora na sombra também ocorreu a emergência, mas em menor proporção (69%). Entretanto, o índice de recrutamento na sombra foi de 1,5% enquanto a pleno sol foi de 96,9%. Estes resultados indicam que as sementes de Tecoma stans germinam e recrutam suas plântulas em ambientes abertos confirmando o potencial invasor da espécie.

The effects of the temperature and light on the control of seeds germination in Tecoma stans was studied in the present work. The influence of constant temperatures from 10 to 45ºC, with 5ºC intervals, under the white light and darkness were tested. The optimum temperature for the germination of the seeds was between 25 and 30ºC, for both the light and the dark treatments. The maximal germination was reached in the range of 15 to 35ºC under the light and of 20 to 40ºC in the darkness. The seeds showed highest synchronization of the germination near the optimal temperature. The germination in the field was tested under the two light conditions. The highest percent of germination occurred under the direct sunlight (86.1%) than under the canopy (69%). However, under the canopy, the seedling presented 1.5% of the recruitment, while under the direct sunlight, 96.9 %. Results showed that T. stans seeds germinated well in the open areas with the occurrence of high seedling recruitment indicating the invasion potential of the species in such light conditions.
Keywords: Tecoma stans; cardinal temperatures; seed germination; invasion potential